2020
DOI: 10.1080/17538947.2020.1738569
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal event detection: a review

Abstract: The advancements of sensing technologies, including remote sensing, in situ sensing, social sensing, and health sensing, have tremendously improved our capability to observe and record natural and social phenomena, such as natural disasters, presidential elections, and infectious diseases. The observations have provided an unprecedented opportunity to better understand and respond to the spatiotemporal dynamics of the environment, urban settings, health and disease propagation, business decisions, and crisis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 206 publications
0
36
0
Order By: Relevance
“…Take one finding, the relative humidity (RH) was largely in the range of 45-85% in affected areas, for example, relative humidity can be set into this range in the ABM for simulating COVID-19 outbreak. We are conducting quantitative analytics to extract the relationships between COVID-19 outbreak and its socioeconomic impacts and a variety of relevant factors as appropriate in a big spatiotemporal data event extraction fashion (Figure 17) (Yu et al 2020), such as economic conditions, temperature and humidity, air quality and UV index, etc., using machine learning, clustering and regression, feature selection, anomaly detection, as well as nonlinear extensions via techniques such as generalized additive models and deep-learning methods.…”
Section: The Forecasting and Strategy Battlegroundmentioning
confidence: 99%
“…Take one finding, the relative humidity (RH) was largely in the range of 45-85% in affected areas, for example, relative humidity can be set into this range in the ABM for simulating COVID-19 outbreak. We are conducting quantitative analytics to extract the relationships between COVID-19 outbreak and its socioeconomic impacts and a variety of relevant factors as appropriate in a big spatiotemporal data event extraction fashion (Figure 17) (Yu et al 2020), such as economic conditions, temperature and humidity, air quality and UV index, etc., using machine learning, clustering and regression, feature selection, anomaly detection, as well as nonlinear extensions via techniques such as generalized additive models and deep-learning methods.…”
Section: The Forecasting and Strategy Battlegroundmentioning
confidence: 99%
“…Results from case studies have shown positive feedback on the proposed downscaling method, demonstrating good quality for simulating spatially distributed precipitation fields and yielding the best performance among all other tested methods through visual inspection and quantitative analyses. It is hard for traditional and machine learning super-resolution based methods to exclude the interpolation process and include the non-linear characteristics of precipitation event into the method design [41]. Meanwhile, many downscaling methods like bicubic interpolation and DeepSD do not have extra constraints to enforce the final outputs to hold rainfall consistency with the initial inputs.…”
Section: Discussionmentioning
confidence: 99%
“…HSR sea ice images captured by satellites or airplanes provide detailed observational data for extracting geophysical attributes of sea ice features, such as floe or melt pond shape, distribution, and coverage. HSR images, however, pose a serious challenge for discovering spatiotemporal patterns of sea ice from this heterogeneous big data in a timely manner [39]. We design and build the ArcCI system based on cloud computing to handle this big data challenge.…”
Section: Discussionmentioning
confidence: 99%